Polymerization on Heating up of Bio-Oil: A Model Compound Study - Hu, Xun; Wang, Yi; Mourant, Daniel; Gunawan, Richard; Lievens, Caroline; Chaiwat, Weerawut; Gholizadeh, Mortaza; Wu, Liping; Li, Xiang; Li, Chun-Zhu (John Wiley & Sons, Inc., 2013)
Understanding of the condensation reactions in bio-oil is the key for efficient conversion into transportation fuel or value-added chemicals. In this study, the roles of the typical compounds representing the sugars, sugar derivatives, and aromatics found in bio-oil were investigated for their contribution to condensation reactions. Glucose played a key role for the polymer formation due to its decomposition to reactive compounds with multiple hydroxyl groups, carbonyl groups or conjugated bonds. The sugar derivatives, including furfural, hydroxyl aldehyde and hydroxyl acetone, were also found to be reactive toward polymerization. The carboxylic acids were shown to be the catalysts for polymerization and formic acid was much more efficient to catalyze polymerization than acetic acid. The phenolic compounds also promoted the acidcatalyzed reactions. Vanillin contains reactive a carbonyl group, leading to its high tendency toward polymerization. In methanol, various kinds of methanolysis reactions dominated, which significantly suppressed the decomposition of glucoseand the polymerization of other compounds.